The accidental environmentalists: Factors affecting farmers' adoption of pro-environmental activities in England and Ontario. (May 2019) - Marr, Eric Joseph; Howley, Peter
Abstract: Based on semi-structured interviews with 54 distinct actors in the UK and Canada, we identify a range of internal psychological orientations that are common (albeit to varying degrees) in both case study regions that, when taken together, provide a lens through which on-farm decisions relating to pro-environmental behaviours are internally analysed and subsequently operationalised. We label these orientations as Production, Business, Environmental, Lifestyle, and Farm Health . Through these orientations, we find farmers are often becoming 'accidental environmentalists' by undertaking many pro-environmental activities for non-environmental reasons. Prominent examples include adopting environmentally beneficial on-farm decisions to support field sports (i.e. shooting), pursuing production improvements with environmental spin-offs (e.g. cover crops, beneficial pollinators), or seeking improvements to personal or family health and well-being (e.g. reduced use of chemicals). This analysis therefore highlights the importance of not oversimplifying farmer motivations along a dualistic profit-seeking v stewardship divide when it comes to understanding environmental behaviour. Highlights: We explore farmers' pro-environmental decision-making in England and Ontario, Canada. We identify a range of internal orientations that are common in both case study regions. These orientations are Production, Business, Environmental, Lifestyle, and Farm Health. These interests form a frame through which options are internally analysed and decisions derived. Farmers are undertaking many pro-environmental activities for non-environmental reasons.